More than rugby: A scoping review of coaches in rugby - Paul, L.; Davidow, D.; Stodter, A.; Till, K.; Dane, K.; Jones, B.; Hendricks, S. (International Journal of Sports Science & Coaching, 2023)
Introduction It is well-recognised that fulfilling the role of a coach is multi-faceted. In rugby, some of these coaching facets have been studied, however the research has not been reviewed. Reviewing the literature on rugby coaches will inform and guide policies, coach education, research and practice. Therefore, the purpose of this study is to provide a scoping review of the current coach focused literature on rugby union, rugby league and rugby sevens.